THE EFFECTIVENESS OF GAME BRAIN STIMULATION ON PRE-SCHOOL CHILD DEVELOPMENT IN PAUD BABUSSALAM DS. PANDEAN KAB. TRENGGALEK - Evita Widyawati; Byba Suhita; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2017)
Development child in age preschool very important. Because on age this required for process development self and concept self in himself. In times this for support growth and its development required appropriate stimulation with age and is no make depressed on children. The objective was Knowing effectiveness stimulation brain games to preschooldevelopment child in PAUD BabussalamDesa Pandean KabupatenTrenggalek. The design used in research was quasi-experimental design. Population was child preschool in PAUD BabussalamDesa Pandean KabupatenTrenggalek. The sample ware 26 respondents on simple random sampling. Variables Independent research was stimulation brain games and variable dependent was development motor. Data collected with using DDST, then the data was analyzed use test Wilcoxon with level significance α ≤ 0, 05. Results research show that brain stimulation affects the game on significant on smooth motoric (p = 0.025), and coarse motor(p = 0.046), but no influence on development language (p = 0.317) and psychosocial (p = 0.317). Before given the brain game, many respondents have DDST normal value as much as 21 respondents (80.8%), and the suspect five respondents (19.2%), while after given brain game that suspect DDST value decreases became one respondent (3.8%). Results test statistics use Wilcoxon Signed Test Range obtained that p = 0.046, which means that affects the brain game on significant DDST against children. Conclusion from research this was Brain Game is effective in improving the ability of Childhood Development Pre-School.